The Effect of Incentives on Employee's Work Effectiveness at PT. United Coconut Tina Indonesia, North Minahasa - Syafiah Nurchamiddin; Mareyke G.V Sumual; M. Salindeho MP (AIBPM Publisher, 2020)
This study aims to determine the effect of incentives upon employees' work effectiveness at PT. United Coconut Tina Indonesia, North Minahasa. This study made use of associative method with the quantitative approach. The data were collected by questionnaires distributed to employees in PT. United Coconut Tina Indonesia, North Minahasa to find the causes and consequences of the variables. The population used in this study is the employees of PT. United Coconut Tina Indonesia, North Minahasa. This study applied a simple linear regression analysis through the requirements test including the instrument test and normality test. The data derived from questionnaires where been weighted and processed using the SPSS version 22. The findings lead to a conclusion that incentives affect work effectiveness.